(untitled) (Journal Of Educational and Psychological Researches, 2016)
This research aims to find out the relationship of risk behavior & job satisfaction for workers in the emergency program in the international relief agency (UNRWA) in the Gaza Strip and the level of each of them, and to achieve that we have been conducting research on the strength of "210" sample employees of the emergency program staff in the international relief agency in Gaza governorates, and try to answer the research questions the researcher through the use of measurements of risk behavior and job satisfaction are two of the researcher, The researcher has used several statistical methods to identify the validity and reliability of scales and access to research and interpretations of the results, and these methods: the mean, standard deviation and relative weight, Pearson correlation coefficient, test "t", scheffe test, variance and variance analysis bilateral analysis test (2 × 2), results showed that the level of risk-taking behavior is located at the average level of relative weight (68.5%), and job satisfaction level is at a good level relative weight (73.5%) among respondents, as well as the presence of a statistically significant relationship between job satisfaction and risk taking behavior in general, and the presence of statistically significant differences in the level of risk-taking behavior is attributable to gender, educational qualification, the nature of the profession, the workplace, and to maintain, and the lack of statistically significant differences in the level of risk-taking behavior attributed to marital status, years of experience, and the lack of statistically significant differences in the level of satisfaction differences career due to the variable gender, marital status, educational qualification, years of experience and the workplace, and the presence of significant differences in the level of job satisfaction differences due to the variable nature of the profession, the province, and the presence of the effect statistically significant interaction between gender "male, female" job satisfaction "low , high "after the distinctive capabilities of personal risk, while the results did not show statistically significant impact indicative of the rest of the dimensions of the total degree of risk taking behavior have, And the existence of the effect statistically significant interaction between qualification and job satisfaction "low, high," a motivated risk, while the results did not show significant influential statistically for the rest of the overall dimensions and the degree of risk taking behavior they have, and the presence of the effect statistically significant interaction between the nature of the profession and job satisfaction "low, high "Just risk decision-making, while the results did not show significant influential statistically for the rest of dimensions and the total score for the behavior of the risk they have, and the presence of the effect statistically significant interaction between the workplace and job satisfaction" low, high, "the dimensions accept the risk, and the motives of the risk, while not shown Results statistically significant effect on the rest of the dimensions of the total degree of risk taking behavior.